Friction and wear behavior of different seal materials under water-lubricated conditions - Weigang Zhao; Guoyuan Zhang; Guangneng Dong (Friction)
Abstract The shaft mechanical face seal in a high-speed turbopump of a liquid rocket engine often operates under extremely harsh conditions. For example, a low-temperature and low-viscosity fluid (such as liquid oxygen or liquid hydrogen) is used as a lubricant. The performance of the seal rings, especially the friction and wear behavior, directly determines whether the seal functions normal. In this study, the friction and wear behavior of several ring materials are tested using a pin-on-disk tribo-tester, and the wear morphology of the ring is investigated. The friction coefficients (COFs) and mass-wear rates under dry-friction and water-lubricated conditions, which are used to simulate low-viscosity conditions, are obtained. The results show that at a pressure-velocity (PV) value of 2.4 MPa·(m/s), the COF between the copper graphite (stator) and copper-chrome alloy disk (rotor) is low (with a value of 0.18) under the dry-friction conditions, and the 5-min wear mass of the copper graphite is approximately 2 mg. Under the water-lubricated conditions, compared with other materials (such as copper-chrome alloy, S07 steel, alumina ceramic coating, and nickel-based calcium fluoride), the S07 steel with a diamond-like carbon film is preferred for use in a high-speed turbopump under extreme conditions. The results of this study can provide theoretical and experimental guidance in the design of mechanical face seals in liquid rocket engines.